A 0.8V, 152 μW, 433 MHz Mixer-First Receiver with a Self-Adjusted Frequency Tracking Loop - Chuan-Yi Wu; Yen-Ting Chen; Yu-Te Liao (IEEE Access, 2021)
This paper presents a 433 MHz low-power receiver utilizing an N-path filter technique and a self-frequency tracking mechanism. Without the front-end amplifier, the mixer-first architecture can reduce power consumption significantly. A self-adjusted frequency tracking loop (SA-FTL) adjusts local oscillator (LO) frequency to approach input RF frequency automatically, thereby enhancing conversion gain and lowering return loss. The receiver, implemented in a $0.18~μ \text{m}$ CMOS process, achieves a sensitivity of −80 dBm at a bit error rate (BER) of 10−3 and a data rate of 10 kb/s, while consuming $152~μ \text{W}$ from a 0.8V voltage supply.